KEBERHASILAN APLIKASI PEDULI LINDUNGI TERHADAP KEBIJAKAN PERCEPATAN VAKSINASI DAN AKSES PELAYANAN PUBLIK DI INDONESIA - Aridyah Fastyaningsih (Departemen Administrasi Publik, Universitas Diponegoro, 2021)
COVID-19 now is a pandemic that is happening in many countries in the world. The government's policy by vaccination program is the main objective of reducing the number of Corona Virus transmissions and efforts to restore the national economy. Indonesian government has launched the PeduliLindung application to help the government dive COVID-19 problem in Indonesia. This application was introduced directly by the Ministry of Communication and Information Technology. PeduliLindung application was created as an effort to reduce the COVID-19 virus. The way this application works relies on the participation of the community. Through this application, we can find out the data on the results of the Covid-19 examination and national vaccination data because it is already integrated in the application. The purpose of this study was to determine the success of the PeduliLindung application in accelerating vaccination and access to public services in Indonesia. This study uses a qualitative descriptive method. The results of this study indicate that the PeduliLindung application is effective in supporting the accelerated vaccination policy, although there are pros and cons and some fraud in its implementation.Keyword: Success, Policy, Accelerating, Services